Plainview : The Enigmatic Paleoindian Artifact Style of the Great Plains - Knudson, Ruthann; Johnson, Eileen McAllister; Holliday, Vance T. (Book collections on Project MUSE., 2017)
"The Plainview Paleoindian artifact style was first recognized in 1947, after numerous projectile points were found during excavations of a bison kill site near Plainview, Texas. In the decades that followed, however, Plainview became something of a catch-all category with artifacts from across the continent being lumped together based merely on gross similarities. This volume unravels the meaning of Plainview, detailing what is known about this particular technology and time period. Contributing authors from the United States and Mexico present new data gleaned from the reinvestiga- tion of past excavations, notes, maps, and materials from the original Plainview site as well as reports from other Plainview Paleoindian sites across the Great Plains, northern Mexico, and the southwestern United States."--Provided by publisher.